Compulsory land acquisition and voluntary land conversion in Vietnam : (The World Bank, 2011)
The objective of the study was to assess the issues relating to involuntary and voluntary land conversion in the current laws and policies, and the implementation of these laws, and to propose improvements to be considered in the preparation of the law on amendments and supplementations of the Land Law scheduled to be placed before the National Assembly in 2013.